Use of a Neurosensorimotor Reflex Integration Program to Improve the Sensory-Motor Sphere Functions of Children with Down Syndrome - Svetlana Masgutova; Ludwika Sadowska; Joanna Kowalewska; Denis Masgutov; Nelli Akhmatova; Henryk Filipowski (Medical Science: Trends and Innovations Vol. 11, 2025)
Down syndrome, first described by John Langdon Down in 1866, is a genetic disorder characterized by the presence of an additional chromosome 21 due to nondisjunction during gametogenesis and is reportedly the most common chromosomal abnormality in humans. This anomaly presents with intellectual impairment, growth limitations, and distinct facial features. While improvements in medical care have led to increased life expectancy for those with Down Syndrome, therapies for cognitive disabilities often emphasize pharmacologic strategies. Consequently, there is a need for alternative or complementary therapies for addressing the neurodevelopmental deficiencies of children with Down syndrome. Therefore, a novel and non-invasive method for evaluating and improving neurodevelopmental delays in children with Down syndrome was evaluated. Changes in the reflex patterns of children (6 months to 18 years old) (n=54) with Down syndrome were used as objective measures for comparing before and after participation in a Neurosensorimotor Reflex Integration exercise program. Initial reflex scores of children in the Study Group ranged from severe dysfunction to low levels of development. After the program, the majority number of reflex patterns showed substantial improvement after children’s completion of the exercise program, although not to the level of development comparable to that of children with typical development. This success indicates that the neurodevelopment and overall functioning of Down syndrome children are not static and can be improved with this novel Masgutova Neurosensorimotor Reflex Integration (MNRI®) exercise program. This research also shows the fact that the changes in reflex patterns happen in children with mild, moderate and severe disabilities on a significant level. In future, research will explore the long-term effects of MNRI intervention on neurophysiological and biomechanical mechanisms in children with Down syndrome, along with a focus on enhancing motor functions, cognitive processes, and emotional regulation.